The ancient city between Archaeology and History: an interview with Rebecca Sweetman - Sweetman, Rebecca; Furlani, João Carlos (Romanitas - Revista de Estudos Grecolatinos, 2023)
Interview with Rebecca Jane Sweetman, a renowned Irish researcher specializing in the archaeology of Roman Greece and Late Antiquity. Currently, she holds the position of Professor of Ancient History and Archaeology at the University of St Andrews, where she previously led the School of Classics. In September 2022, she assumed the role of Director of the British School at Athens, having previously served as Assistant Director from 2000 to 2003.
Keywords: Ancient city; Archaeology; History; Interview; Rebecca Sweetman